Similarity Measures Based on q-Rung Linear Diophantine Fuzzy Sets and Their Application in Logistics and Supply Chain Management. (20th January 2022) - Qiyas, Muhammad; Naeem, Muhammad; Abdullah, Saleem; Khan, Neelam; Ali, Asad
Abstract : With the frequent occurrence of emergency events, decision-making (DM) plays an increasingly significant role in coping with them and has become an important and the challenging research focus recently. It is critical for decision makers to make accurate and reasonable emergency judgments in a short period as poor decisions can result in enormous economic losses and an unstable social order. As a consequence, this work offers a new DM approach based on novel distance and similarity measures using q -rung linear Diophantine fuzzy ( q -RLDF) information to assure that DM problems may be addressed successfully and fast. One of the useful methods for determining the degree of similarity between the objects is the similarity measure. In this paper, we propose some new q -rung linear Diophantine fuzzy ( q -ROLDF) distances and similarity measures. The Jaccard similarity measure, exponential similarity measure, and cosine and cotangent function-based similarity measures are proposed for q -LDFSs. The defined similarity measures are applied to the logistics and supply chain management problem, and the results are discussed. A comparison of new similarity measures is developed, and the proposed work's advantages are discussed.